2013
DOI: 10.5125/jkaoms.2013.39.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective clinical study on sinus bone graft and tapered-body implant placement

Abstract: ObjectivesThis study evaluated implant success rate, survival rate, marginal bone resorption of implants, and material resorption of sinus bone graft in cases wherein tapered body implants were installed.Materials and MethodsFrom September 2003 to January 2006, 20 patients from Seoul National University Bundong Hospital, with a mean age of 54.7 years, were considered. The mean follow-up period was 19 months. This study covered 50 implants; 14 implants were placed in the maxillary premolar area, and 36 in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Herzberg et al 21 examined 70 patients with 212 implants placed in 81 maxillary sinus regions during the period 1995 to 2000 and reported 95.5% and 83.7% cumulative survival and success rates, respectively, for 4.5 years. The study of Kim et al 27 showed that the mean marginal bone resorption around the implants was 0.69 mm 1 year after prosthodontic loading. Marginal bone resorption of more than 1.5 mm occurred in 9 implants, for a success rate of 88%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Herzberg et al 21 examined 70 patients with 212 implants placed in 81 maxillary sinus regions during the period 1995 to 2000 and reported 95.5% and 83.7% cumulative survival and success rates, respectively, for 4.5 years. The study of Kim et al 27 showed that the mean marginal bone resorption around the implants was 0.69 mm 1 year after prosthodontic loading. Marginal bone resorption of more than 1.5 mm occurred in 9 implants, for a success rate of 88%.…”
Section: Discussionmentioning
confidence: 97%
“…The study of Kim et al27 showed that the mean marginal bone resorption around the implants was 0.69 mm 1 year after prosthodontic loading. Marginal bone resorption of more than 1.5 mm occurred in 9 implants, for a success rate of 88%.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies regarding implant survival rates have been published. Sato et al [8] presented that survival rate of 1-piece implants placed in immediate function was 100%, also Kim et al [9] showed that success rate was 92%, and the survival rate was 96.0% in tapered body implant with sinus bone gra . Moreover, Suh et al [10] showed survival rate of ITI TE ® implants was 100% in 3-year clinical study.…”
Section: Introductionmentioning
confidence: 99%
“…Using dental implants for prosthetic rehabilitation of the edentulous maxilla has become a routine dental procedure. However, low quality of the posterior maxillary bone and a highly pneumatised maxillary sinus can compromise an implant's survival 1 2 . Implant migration into the paranasal sinus cavities is a rare but a significant complication.…”
Section: Introductionmentioning
confidence: 99%